To find the intersection of the curve
![y=x(x-1)(x-2)](https://img.qammunity.org/2023/formulas/mathematics/college/heidf55uz7hw9iglxooecixwgpk8fa4w9s.png)
And the x-axis, we first have to notice that the x-axis is the same as the line:
![y=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/5vm2i52uqdka0dixzzefmp92421iv5xkk7.png)
Now, we have a system of two equations.
If we substitute y = 0 into the first, we have:
![x(x-1)(x-2)=0](https://img.qammunity.org/2023/formulas/mathematics/college/xu3mrr52pfinfem35mrp2r5a9opo784b90.png)
Now, for this equation to be true, one of the factors, "x", "(x-1)" or "(x-2)" has to be zero.
So, we will have three solutions:
![\begin{gathered} x=0 \\ x-1=0\leftrightarrow x=1 \\ x-2=0\leftrightarrow x=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jv9ep9vzfy3qlfcllb53o0n8wjwnofewdy.png)
And since these are on the x-axis, we already know that the y values for them are all y = 0.
Thus, the points of intersections are:
![\begin{gathered} (0,0) \\ (0,1) \\ (0,2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7ecu3yfiddm4hym26lc8moofgu36x5owyj.png)